2019
DOI: 10.1038/s41467-019-12739-9
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 activates the kynurenine pathway via increased dosage of interferon receptors

Abstract: Trisomy 21 (T21) causes Down syndrome (DS), affecting immune and neurological function by ill-defined mechanisms. Here we report a large metabolomics study of plasma and cerebrospinal fluid, showing in independent cohorts that people with DS produce elevated levels of kynurenine and quinolinic acid, two tryptophan catabolites with potent immunosuppressive and neurotoxic properties, respectively. Immune cells of people with DS overexpress IDO1, the rate-limiting enzyme in the kynurenine pathway (KP) and a known… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
76
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 72 publications
4
76
0
Order By: Relevance
“…Recently, we reported an analogous activation of the IDO pathway in individuals with Trisomy 21 (Down syndrome) (29). Indeed, 4 of the 6 receptors for interferon-alpha and -gamma are encoded by genes on chromosome 21.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Recently, we reported an analogous activation of the IDO pathway in individuals with Trisomy 21 (Down syndrome) (29). Indeed, 4 of the 6 receptors for interferon-alpha and -gamma are encoded by genes on chromosome 21.…”
Section: Discussionmentioning
confidence: 93%
“…Interestingly, the major effects of COVID-19, in addition of IL-6 levels, were tryptophan metabolism and the kynurenine pathway. The rate-limiting step in this pathway is determined by the enzymatic activity of indole 2,3-dioxygenase (IDO1), a pleotropic enzyme with complex effects, including an immunoregulatory role (29). In general, the kynurenine/tryptophan ratio is a general measure of IDO activity, although the meaning of this measure alters depending upon the dynamics of metabolism and its effects on half-lives of kynurenine and tryptophan.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We recently discovered that trisomy 21 (T21), the genetic cause of DS, causes consistent activation of the IFN transcriptional response in multiple cell types (12)(13)(14)(15), which is explained by the fact that four of the six IFN receptors are encoded on chromosome 21 (IFNAR1, IFNAR2, IFNGR2, IL10RB). Additional investigations of the proteome (16), metabolome (14), and immune cell lineages (13,15) of people with DS demonstrated that T21 causes: 1) changes in the circulating proteome indicative of chronic autoinflammation with clear dysregulation of IFN-inducible cytokines (16), 2) activation of the IFN-inducible kynurenine pathway, leading to elevated production of neurotoxic tryptophan catabolites (14), and 3) widespread hypersensitivity to IFN stimulation across the human immune system (13,15). Altogether, these results support the notion that DS can be understood in good measure as an interferonopathy, whereby increased IFN signaling could account for many of the developmental and clinical impacts of T21.…”
Section: Introductionmentioning
confidence: 99%